FgAP‐2 complex is essential for pathogenicity and polarised growth and regulates the apical localisation of membrane lipid flippases in Fusarium graminearum. (17th June 2019) - Zhang, Jing; Yun, Yingzi; Lou, Yi; Abubakar, Yakubu Saddeeq; Guo, Pusheng; Wang, Shumin; Li, Chunling; Feng, Yuan; Adnan, Muhammad; Zhou, Jie; Lu, Guo‐dong; Zheng, Wenhui
Abstract: AP‐2 complex is widely distributed in eukaryotes in the form of heterotetramer that functions in the uptake of membrane proteins during mammalian/plant clathrin‐mediated endocytosis. However, its biological function remains mysterious in pathogenic fungi. In this study, the wheat scab fungus, Fusarium graminearum, was used to characterise the biological function of the AP‐2 complex. Our study shows that FgAP‐2 complex plays a critical role in the maintenance of hyphal polarity. Lack of any subunit (FgAP2 α, FgAP2 β, FgAP2 σ, and FgAP2 mu ) of the FgAP‐2 complex significantly affects the fungal vegetative growth, conidial morphology, and germination. Remarkably, FgAP‐2 complex is important for the fungal pathogenicity, especially during colonisation and extension after infecting the host. The FgAP‐2 complex is expressed ubiquitously at all developmental stages but having more concentrated protein distribution at the subapical collar and septa in young growing hyphae. Although FgAP‐2 complex displays similar dynamic behaviour to the actin patch components and accumulates at endocytic sites, it is dispensable for general endocytosis. We further demonstrated that FgAP‐2 complex is required for polar localisation of the lipid flippases FgDnfA and FgDnfB, which led to the proposal that FgAP‐2 functions as a cargo‐specific adaptor that promotes polar growth and colonising ability of F . graminearum .